Transformasi Pendidikan Sains sebagai Penggerak Kompetensi Masa Depan Siswa Sekolah Dasar - Citra Raflesia; I Wayan Suastra; I Made Citra Wibawa; Ida Bagus Putu Arnyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to explore the role of science education in elementary schools in developing scientific thinking, science literacy, and 21st-century skills. The method used is a literature review through the analysis of various sources related to science education. The results indicate that science education is not merely a medium for transferring natural concepts, but also a means to foster scientific character, critical thinking, and creativity. The integration of technology, inquiry-based approaches, and project-based learning has been proven to enhance students' readiness for the digital era. In conclusion, science education requires curriculum transformation and capacity building for teachers to manage learning that fosters future competencies. Keywords: Critical Thinking, Science Education, Science Literacy, Technology Integration, 21st-Century Learning